CHANGES IN THE FUNCTION AND ARCHITECTURE OF LUMBUNG IN BALI HOUSEHOLDS IN SADING CUSTOMARY VILLAGE, BADUNG, BALI - Ni Made Emmi Nutrisia Dewi; Putu Rumawan Salain; I Made Suastika; I Nyoman Sukiada (Cultural Studies Doctorate Program, Postgraduate Program of Udayana University, 2020)
Lumbung or granary is a building that serves as a place to store rice. In some houses in the Sading Traditional Village, the granary is one of the buildings which is generally located near the kitchen. However, at present, this granary in Sading Traditional Village has changed its function and architecture as part of the dynamics of modern life. Seeing this condition, it is necessary to conduct research on the architecture of the barn in Sading Traditional Village. The purpose of this study was to determine the form of change, the causes and meanings contained in the phenomenon of changing the function and architecture of the granary in Balinese houses in Sading Traditional Village. The method used in this research is a qualitative approach with the perspective of cultural studies. The results showed that there was a change in the function of the barn which was previously only a place to store rice, but now the function of storing rice is only as a symbol, while other functions are mostly used as a multipurpose room such as a place to entertain guests during religious ceremonies, a place to relax and other activities. While the architectural changes lie in the materials, decorations and others that follow current developments. The main cause is the livelihoods of the people of the Adat Sading Village who no longer work as farmers. Besides that, it is due to ideological factors and beliefs, economics and the development of science and technology. The meanings contained in these changes include religious, aesthetic, image and cultural preservation. Keywords: Change, Function, Architecture, Granary, meaning